Eficacia de los enjuagatorios con agua ozonizada en el control de los niveles de placa bacteriana y de streptococcus mutans en cavidad oral - Sánchez Barrueto, Cristina Luz (2009)
It was made an experimental, prospective and longitudinal study. The aimed of the study was to determine the effectiveness of ozonated water rinse to control plaque level and Streptococcus mutans level in oral cavity. It was worked with a sample of 66 students from 6 to 9 years old from Juan Velasco Alvarado Nº80015 school, randomly divided into two groups A and B (rinsing for 30 and 60 seconds respectively), where any of the group was the control of the other. First of all it was taken a sample to determine the Streptococcus mutans level and the plaque level according to the index of O'Leary. After four weeks of application of ozonated water rinse during 30 or 60 seconds each time, it was taken another sample to assess the two levels mentioned above. The mouthwash was considered effective when the plaque level and CFU counts of Streptococcus mutans were both lower than the initial one. It was applied the t-student test for paired data. The mouthwash during 30 and 60 seconds decreased the plaque level from 74,3% to 45%; and from 77,9% to 35,4% respectively; while the level of Streptococcus mutans decreased from 171,9 x 106 UFC/ml to 40,5 x 106 UFC/ml and from 178,9 x 106 UFC/ml to 29,2 x 106 UFC/ml respectively. We conclude that ozonated water rinses are significantly effective in controlling the plaque level and the Streptococcus mutans levels in the oral cavity.